Halal cosmetics and consumer behavior: Insight from Millennials - Febrina Mahliza; Prita Prasetya (Journal of Enterprise and Development (JED), 2024)
Purpose — This study aims to analyze the consumption behavior of halal cosmetic products, focusing on factors such as halal certification, trust, and awareness of halal practices.Method — The population for this research comprises residents of Jakarta who fall within the millennial generation category (born between 1980-2000). The research sample size will consist of 170 respondents selected through purposive sampling techniques. Data collection will be conducted through questionnaires, and the analysis will be performed using the Partial Least Square (PLS) analysis method.Result — Based on the study's findings, it can be concluded that halal certification has a positive and significant impact on both halal trust and awareness. Additionally, trust exhibits a positive and significant influence on the consumption of halal products, indicating that higher consumer trust is associated with increased consumer behavior in consuming halal cosmetic products. However, it was observed that halal awareness does not significantly affect consumption behavior. This implies that an increase in halal awareness does not necessarily correspond to a higher likelihood of consuming halal cosmetic products.Novelty  — The unique contribution of this research lies in its focused analysis of the consumption behavior associated with halal products. This study builds upon previous research by delving into specific variables that impact behavior, particularly within the context of halal cosmetic products.